NAVIGATING THE DIGITAL DIVIDE: ACCESS, EQUITY, AND SOCIAL INCLUSION IN THE INFORMATION AGE - Saifuddin Zuhri; Cholid Fadil (Social Studies and Humanities Journal (SOSHUM), 2025)
The digital divide is a critical issue that affects access to technology and information, especially among vulnerable groups. This research aims to evaluate the effectiveness of programs and policies implemented to reduce the digital divide and increase equality of access. This study focuses on analyzing the factors that influence the success of digital interventions in various social and economic contexts. The approach used is Systematic Literature Review (SLR) by collecting and analyzing 24 articles from reputable international journals. Data was extracted and analyzed using thematic analysis to identify key patterns and trends in the research that has been conducted. Findings show that program success is strongly influenced by technological infrastructure, digital literacy, and collaboration between the public and private sectors. In addition, evidence-based policies and community participation have been proven to increase the effectiveness of interventions in reducing the digital divide. This research makes a significant contribution to the development of digital divide theory by emphasizing the importance of a multidimensional approach. The practical implications of these findings can be used to design more inclusive and effective policies in overcoming the digital divide in various regions and societal groups.